From Face-to-Face to Virtual Interactions: Unraveling the Impact of Technological Advancements on Conformity and Consumer Buying Patterns - Alvin Novaldo; Hommy Dorthy Ellyany Sinaga; Marlo C. Novino; Jupert Jasser G. Abellana (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study examines the impact of technological advancements and conformity theory on consumer buying patterns in the digital era. As social interactions and commerce increasingly shift online, understanding the underlying factors influencing consumer decisions becomes essential. Utilizing a quantitative approach, data were collected from 269 members of a youth community through structured questionnaires. The analysis employed multiple linear regression techniques to explore significant relationships among variables. Findings reveal that technological advancements significantly enhance information accessibility and shopping experiences, facilitating faster and more informed purchasing decisions. Furthermore, conformity theory is shown to critically shape buying behavior, with individuals often aligning their choices with group norms. These insights underscore the importance for marketers and companies to leverage technology and social influence dynamics to craft effective marketing strategies, ultimately enhancing consumer engagement and satisfaction in the digital marketplace. This research contributes to the understanding of consumer behavior in the context of rapid technological change and collective social influence.